The Impact of Assets Size and Profitability on Funded Status of Employee Retirement Benefits by Quoted Firms in Nigeria - Oluwatoyin, Sule Kehinde; ., Emerole Gideon Ahamuefula (Information Management and Business Review, 2011)
This study assesses the impact of quoted companies’ assets size and profitability on employee retirement benefits in Nigeria. In line with the objective, a hypothesis was formulated. The population of the study is 182 firms quoted on the first- tier market of the Nigerian Stock Exchange and ten (10) quoted firms selected as sample size based on judgmental sampling. The study utilized data from secondary source. Data were obtained from the annual accounts and reports of the (10) quoted firms that made up the sample of the study. The time frame for the study is ten years, covering the period of 1998 to 2007. The technique of analysis used in the study was Multiple Regression Analysis. The study established that the ability of quoted firms to fund their pension costs has direct relationship with their assets sizes and respective profitability. The study recommended an effective monitoring/supervision and enforcement of the provisions of the Pension Reform Act, 2004, in addition to effective implementation of the penalties provided by the Act on non-compliers regardless of their status or origin. The study calls the Government to create conducive and enabling environment for smooth implementation, compliance and application of the Pension Reform Act, 2004 by firms and other players in pension administration. While, regulatory authorities must encouraged research and activities geared towards developing not only accounting policies that would ensure full compliance with Statement of Accounting Standards 8 (SAS 8) but strategies that would ensure optimum investments that enhance net worth and earnings of firms.